EVALUASI TINGKAT MATURITAS DAN USULAN PERBAIKAN MANAJEMEN RISIKO DENGAN MODEL RIMS RISK MATURITY MODEL PADA PT X - INTAN ROSIANA , ARMEINA
Nowadays, communication is a necessity that must be fulfilled by society. It can be seen from telecommunication industry that continues to grow and become one of the government’s main concern. The development of the communication technology depends on telecommunication infrastructure itself. Companies engaged in the telecommunications infrastructure compete closely to provide the best offer to customers. Somehow, a business will certainly face various risks that pose a threat to its business sustainability. Therefore, companies must have a good risk management system. PT X is aware that the risks can slow down the company to achieve their objective. Because of this, a risk management maturity measurement is needed to see the application of risk management that has been implemented by the company. The risk management maturity measurement conducted in this study uses the RIMS Risk Maturity Model model developed by Minsky & Fox (2015). This model has seven main attributes that will be used to measure risk management maturity. These attributes include an ERM-based approach, ERM process management, risk appetite management, root cause discipline, uncovering risks, performance management, and business resilience and sustainability. Maturity measurement is conducted using a questionnaire distributed to several respondents who understand and has a direct role in the implementation of risk management in PT X. From the distribution of questionnaires to nine respondents, the results for the attributes of ERM-based approach is 2.80, ERM process management attribute is 3.16, the risk appetite management attribute is 3.16, the root cause discipline attribute is 3.34, the uncovering risk attribute is 3.25, performance management attributes worth 3.16, and business resilience and sustainability attributes worth 3.30, from a maximum scale of 5. These results were then validated with the actual condition of PT X and based on the characteristics of the level owned by RIMS RMM. It was found that the risk management maturity level of PT X is at Level 2: Initial. These conditions indicate that the company has implemented risk management in a structured manner but hasn’t been implemented by all functions of the company. Based on these results, PT X need to increase the risk management maturity to a higher level by training employees so that the risk management culture is owned by each employee and conducting quantitative analysis on the risk management process in the form of financial calculations to help PT X make decisions in managing risks.